Role of Botulinum toxin injection in neurological problems: A Short Review - Dhungana, Isha; Shrestha, Prabin (Nepal Journal of Neuroscience, 2016)
Botulinum Toxin (BoNT), a neurotoxin known for many years for its lethal nature has been in use for many cosmetic purposes for last many years. Its use in many medical problems especially chronic neurological problems has been well established in recent years. BoNT is a useful symptomatic treatment for many neurological disorders, and is emerging as one of the leading modes of treatments in the new subspecialty in neurology called “Interventional neurology.” We have also been using BoNT regularly for therapeutic purposes in different neurological diseases with good success rate for last few years. We think use of BoNT-A needs to be encouraged in our country to provide relief to the patients suffering from many of the chronic disabling neurological problems.Nepal Journal of Neuroscience 12:3-7, 2015